Peculiarities of the influence of conflict culture and personal competence on the confrontational modus operandi in conflict relations - N. I. Pryanikova (Вестник университета, 2022)
The article analyses the problems of the formation of conflict interactions and relationships caused by the influence of conflictological culture and competence of the individual, which in recent years has become a priority. The article is based on the methodology of an integrated approach and system analysis. The theoretical basis of the article was the publications of Russian and foreign researchers devoted to conflict-related issues. The research methods used were a review of theoretical works and empirical research, comparative analysis, expert assessments, normative and logical methods. The analysis of methods, mechanisms, tools and other aspects of effective conflict management was carried out. Based on the results generalisation, the main directions of influence of conflictological culture and personal competence on the confrontational mode of conflict relations have been formulated. The conflict consequences determination by personal components of the participants in the conflict interaction is considered separately. In conclusion, the conflict management matrix is presented.